La tercera ruta : una apuesta metodológica de indagación en torno al cuerpo y la motricidad (2011)
ABSTRACT: The article is structured from methodological considerations raised in the local research experience, fulfilled by the group Somatic Culture. These read the conception of the world, the human being, the body, motor skills, knowledge and social function, which can and must guide the inquiry, to get to promote an appropriate alternative and, why not, its own research in the area. The dissertation unfolds in three stages: 1) after the pattern of linear architecture which allows considering, arguing, deriving and concluding, 2) presents some contemporary notions that substantiate and alternative path in research; 3) transits the path laid by the Somatic Culture group local studies, which account for some methodological adjustments and creations around the subject of study body moor skills in situ.